2004
DOI: 10.1103/physreve.70.011502
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin scattering study of salol: Exploring the effects of rotation-translation coupling

Abstract: Brillouin scattering in liquids composed of optically and mechanically anisotropic molecules is affected by coupling between rotational and translational dynamics. While this effect has been extensively studied in depolarized (VH) scattering where it produces the "Rytov dip," recent theoretical analyses by Pick, Franosch show that it should also produce observable effects in polarized (VV) scattering [Eur. Phys. J. B 31, 217 (2003)]; 31, 229 (2003)]]. To test this theory, we carried out Brillouin scattering st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…One of a very powerful tool in studies of glasses is Brillouin spectroscopy since it has been shown to give valuable information on the dynamical properties of glass-forming materials in the gigahertz region. [1][2][3][4][5][6][7][8] The relaxational processes have been extensively studied for glass formers without directional bonds, which show a similar high increase of viscosity upon supercooling and are called fragile systems. 3,6,7 The dynamics of these fragile systems is relatively well understood on the basis of mode coupling theory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of a very powerful tool in studies of glasses is Brillouin spectroscopy since it has been shown to give valuable information on the dynamical properties of glass-forming materials in the gigahertz region. [1][2][3][4][5][6][7][8] The relaxational processes have been extensively studied for glass formers without directional bonds, which show a similar high increase of viscosity upon supercooling and are called fragile systems. 3,6,7 The dynamics of these fragile systems is relatively well understood on the basis of mode coupling theory.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The relaxational processes have been extensively studied for glass formers without directional bonds, which show a similar high increase of viscosity upon supercooling and are called fragile systems. 3,6,7 The dynamics of these fragile systems is relatively well understood on the basis of mode coupling theory. 6,9 On the other hand, in the presence of directional bonds the temperature variation of viscosity is weaker, and the dynamics of these so-called strong and intermediate glass formers is still not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The same is true in the case of metatoluidine 15 for s ͑t͒, ͑t͒, and L ͑t͒. For instance, in the molecular liquid salol, it has been recently shown that the relaxation times and stretching coefficients of s ͑t͒ and ⌫͑t͒ are different.…”
Section: ͑43͒mentioning
confidence: 86%
“…With decreasing temperature, these additional features progressively narrow down and eventually collapse in an unresolved single line as a consequence of the viscoelastic behavior of the material, up to the appearance of two transverse acoustic modes (Brillouin peaks) at even lower temperature in the solid state (Patterson 1976). New macroscopic and microscopic theoretical analyses of scattering from coupling of molecular rotation-translation dynamics of anisotropic molecular fluids have been recently tested by new experimental observations (Zhang et al 2004). Recently, Brillouin scattering has been used to monitor the time-progress of the photo-induced polymerization of binary mixtures of monomer organic compounds as a function of their composition and of temperature (Ziobrowski et al 2011).…”
Section: Condensed Matter Physicsmentioning
confidence: 99%